v-15=-27

Simple and best practice solution for v-15=-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v-15=-27 equation:


Simplifying
v + -15 = -27

Reorder the terms:
-15 + v = -27

Solving
-15 + v = -27

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + v = -27 + 15

Combine like terms: -15 + 15 = 0
0 + v = -27 + 15
v = -27 + 15

Combine like terms: -27 + 15 = -12
v = -12

Simplifying
v = -12

 

You can always share this solution

See similar equations:

| 3y+6=y-8 | | 15+b=23 | | 26=8+v | | -5n-8(1+7n)= | | 7x+12=3x+25 | | 4x+5=3x+8 | | 3(2x-4)=18 | | 6(x-9)=12 | | 4(x+3)=28 | | 4n+5=85 | | 49-3x=x+21 | | 49-3x=x | | 4n-15=25 | | 6n+7=25 | | 3x+3=2x | | 5x-6=16-6x | | 3x-4=2-3x | | 123-3x=15x+23 | | 5-7x=69-21x | | -6-7x=7x+22 | | 4x+6=-120-10x | | 72-2x=2x+12 | | x-5=2x-9 | | 5x+13=1x-6 | | -22-5x=14-9x | | 3x-2=x+7 | | 76-6x=14-9x | | 3x+7=63-5x | | 2x-7=x-4 | | 2x-7=-4 | | 2x-3=7-3x | | 8x+8=3x-2 | | s-2=10 | | 6x+66=12x+22 | | 5x+4=2x+13 | | 2(2x-5)=12 | | 3(x-4)=8-2x | | 3(2x+3)=40 | | 3(x+7)=9 | | 3(w+2)=9+2w | | 6(z+5)=5z | | -7(y+5)=8-6y | | 2y-1=5y-4y | | 8z+4=9z | | z-6.6=2z | | 6.6=2z | | r-5.6=8.9 | | 12x-2=2(3x+5)+21 | | 12x-6=2(4x+8) | | 16x-2=4(3x+7) | | 3r-14=7 | | 12x+7=7x+22 | | 10x-25=65 | | 8x+9=41 | | 8.2(x+1.9)=6.9(x-8.7) | | 7y-3=25 | | 7y-3=15 | | 4x+3=5x | | 6x+5=3x-10 | | 2x+5=23 | | 5x+8=-7 | | 4x-5=27 | | y=2x+3 | | .4*r-1.2=.3*r+.6 | | -10=-14v+-14v |

Equations solver categories